The Influence of Hedonic Motivation, Facilitating Conditions, and Behavioral Intention on the Use of Shopee Paylater Behavior Among Gen Z Moderated by Gender - Ryan Christian; Siti Nurjanah (Universitas Pelita Harapan, 2024)
The digital era has significantly changed consumer shopping behavior, with digital financial technology emerging as the fastest growing digital service sector in Indonesia. One of the fastest growing services in this sector is paylater services, which allow payments to be postponed to be settled at a later date. This study investigates the factors that influence the adoption and usage behavior of one of the largest paylater services in Indonesia, Shopee Paylater, among Generation Z, using the Extended Unified Theory of Acceptance and Use of Technology (UTAUT) model as the basis for this study. This study identifies key factors such as hedonic motivation, facilitating conditions, behavioral intention, and use behavior, with gender as a moderating variable. The purpose of this study is to provide insight into Gen Z consumer behavior in adopting Shopee Paylater, as well as to help paylater service providers understand, adapt, and optimize their products for this demographic. The results of this study indicate that the hedonic motivation and facilitating conditions variables influence the behavioral intention to adopt Shopee Paylater services, and the facilitating conditions and behavioral intention variables influence the use behavior of Shopee Paylater users. The moderating variable in the form of gender asslso has an important role in determining the intention to adopt Shopee Paylater services.